Voice over IP systems and solutions - Swale, Richard (London, United Kingdom Institution of Engineering and Technology, 2001)
This section explores the introduction to voice-over-IP, VOIP voice quality, signalling transport protocols, VOIP gateways, bearer-independent call control; VoIP and multimedia with H.323; session initiation protocol; VoIP clearinghouses and the open settlement protocol and; hybrid PSTN/VoIP.
Electronic reproduction.
Keywords: Internet telephony; Electronic books